Glycated Hemoglobin (HbA1c) Concentrations Among Children and Adolescents With Diabetes in Middle- and Low-Income Countries, 2010–2019: A Retrospective Chart Review and Systematic Review of Literature - Chen, Xiuli; Pei, Zhou; Zhang, Miaoying; Xu, Zhenran; Zhao, Zhuhui; Lu, Wei; Chen, Linqi; Luo, Feihong; Chen, Ting; Sun, Chengjun (Frontiers in Endocrinology, 2021)
Objectives: To explore the glycemic control (represented by glycated hemoglobin [HbA1c] concentrations) in children with diabetes mellitus (DM) in east China and middle- and low-income countries, from 2010 to 2019. Methods: Retrospective data of children with DM from two hospital-based health records were reviewed. Data on HbA1c concentrations, hospitalization due to diabetic ketoacidosis, and patient demographics were collected and analyzed. A systematic review was subsequently performed to analyze publications that report HbA1c concentrations in patients aged <18 years. Patients’ characteristics extracted from each publication were used to generate simulated individual data for pooled analysis. HbA1c estimates were derived from steady-state iterations. Results: Data of 843 diabetic children (aged 11.2 ± 3.9 years) with 2658 HbA1c measures were retrieved from the two hospitals during the period 2010–2020. The duration of diabetes in the patients was 4.4 ± 2.8 years, and their HbA1c was 8.1 ± 2.2%. Patients who were internal migrants had significantly higher HbA1c concentration than resident patients (8.4% vs. 7.9%). The literature review yielded 1164 publications, and the majority (74.1%) of patient data were published in high-income countries. The patient data extracted from these publications generated 486,416 HbA1c concentration estimates between 2005 and 2019. The average HbA1c concentration during the 15 years was 9.07 ± 2.15%. The mean HbA1c concentrations among children were 8.23%, 8.73%, 9.20%, and 10.11% in high-income country (HIC), upper-middle income country (UMIC), lower-middle income country (LMIC), and low-income country (LIC) respectively. The mean rate of optimized glycemic control (HbA1c<7.5%) among children was 32.4%, 27.5%, 21.7% and 12.7% in HIC, UMIC, LMIC and LIC, respectively. Conclusions: The current study indicated that there is substantial room for improvement in glycemic control in children with DM worldwide, especially in middle- and low-income countries.